2010
DOI: 10.1111/j.1439-0272.2009.00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile function and male reproduction in men with spinal cord injury: a review

Abstract: Spinal cord injury (SCI) in men results in defects in erectile function, ejaculatory process and male reproductive potential. There are alterations in the capacity of men with SCI to achieve reflexogenic, psychogenic and nocturnal erections. The sexual function in different stages after SCI and the types of erections depend mainly on the completeness of the injury and the level of neurological damage. Furthermore, most of the SCI men demonstrate defects concerning the entrance of semen into the posterior ureth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 243 publications
(333 reference statements)
2
26
0
6
Order By: Relevance
“…Similar to the results of this research, one study 34 affirms that 60% of the patients had recovered their erection after the SCI, while Ramos et al 35 found that 80% of the patients had erections after the SCI. The erection depends on a combination of the reflex and psychogenic actions and whether they are compromised in the SCI, which will change the erectile response of these patients, as will the influence of psychological factors.…”
Section: 33supporting
confidence: 76%
See 1 more Smart Citation
“…Similar to the results of this research, one study 34 affirms that 60% of the patients had recovered their erection after the SCI, while Ramos et al 35 found that 80% of the patients had erections after the SCI. The erection depends on a combination of the reflex and psychogenic actions and whether they are compromised in the SCI, which will change the erectile response of these patients, as will the influence of psychological factors.…”
Section: 33supporting
confidence: 76%
“…The erection depends on a combination of the reflex and psychogenic actions and whether they are compromised in the SCI, which will change the erectile response of these patients, as will the influence of psychological factors. 7,34 Similar to this study, Reitz et al 26 report that 36% of the males were capable of ejaculating after the SCI. Conversely, another study reports that only 15% of the males were capable of ejaculation after the SCI.…”
Section: 33supporting
confidence: 75%
“…Nevertheless, difficulties generally occur when they try to achieve fatherhood by biological means. Indeed, in SCI patients, three main factors may cause infertility: erectile dysfunction, ejaculatory dysfunction and impaired semen parameters [2,3]. According to two retrospective studies, semen parameters do not significantly decrease during the long-term evolution of SCI patients [1,4,5], which led the authors to conclude that fertility preservation by early sperm banking is not indicated in SCI patients.…”
Section: Introductionmentioning
confidence: 94%
“…[19] Travma, tümör, vasküler hastalıklar, disk hernisi, miyelitler ve multiple skleroz gibi nedenlerle oluşan spinal kord lezyonlarında cinsel işlevler, lezyonun lokalizasyonu ve genişliğine göre etkilenmektedir. [19,[21][22][23][24][25][26][27][28] Spinal kord lezyonları genital cinsel uyarıl-mada gösterilebilir değişikliklere yol açarak orgazma ulaşmayı güçleştirebilir. [27,29,30] Psikojenik ereksiyon işitme, görme, koklama, hissetme ve fantezi sonucu sadece beyinde oluşan uyarılmaların oluştur-duğu ereksiyon olarak kabul edilir.…”
Section: Normal Erkek Cinsel Işleviunclassified
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Torakolomber bölge ile sakral merkezler arasındaki spinal kord lezyonlarında refleks ereksiyonlar görülürken psikojenik ereksiyon oluşmaz. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ancak bu seviyede lezyonu olan olgularda psikojenik ereksiyonların da görülebildiği rapor edilmiştir. Bu durum torakolomber bölgenin altında paravertebral gongliyonlardaki parasempatiklerin normal kalması ve azalmış hipogastrik (sempatik) tonusa bağlı nöroplastite ile açıklanmıştır.…”
Section: Normal Erkek Cinsel Işleviunclassified